Enhancing radial strength and expansion uniformity of iron-based vascular scaffolds: a numerical and experimental investigation on topological optimization - Qiu, Jia; Tang, Luyao; Fu, Wenchao; Qin, Li; Zhang, Deyuan; Wang, Shuhan; Song, Jian (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThin-walled iron-based bioresorbable scaffolds have garnered significant research interest due to their exceptional mechanical properties and favorable biocompatibility. However, current thin-walled iron-based bioresorbable scaffold designs exhibit non-uniform expansion, leading to coating cracking, malapposition, postoperative in-stent restenosis (ISR), and localized pitting corrosion that compromises mechanical integrity.MethodsThis study proposed a dual-factor optimization strategy prioritizing expansion homogeneity through finite element analysis and experimental validation. We systematically modulated the strut width and thickness, as well as the crown radial width in nitrided iron scaffolds, evaluating their mechanical and expansion performance.ResultsIt showed that the optimized (OPT) scaffold maintained comparable radial recoil and foreshortening to the original design while demonstrating significant reductions in maximum principal strain (19.2%) and equivalent plastic strain of expand (19.0%).DiscussionIn vitro expansion experiments confirmed substantially improved expansion homogeneity, while its radial strength (260.07±4.68 kPa) exceeded that of magnesium/polymer scaffolds, achieving parity with CoCr alloy stents. Enhanced expansion homogeneity mitigates coating fracture risks while maintaining clinically sufficient support.